Effect of Ultrasound-Assisted Blanching on Myrosinase Activity and Sulforaphane Content in Broccoli Florets - Mahn-Osses, A; Quintero-Suarez, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Sulforaphane (SFN) is a health-promoting compound occurring in broccoli. It is formed by action of myrosinase in a two-step reaction that also yields undesirable compounds such as nitriles and isothionitriles. Different techniques affecting enzyme activity and tissue integrity were proposed to increase SFN content in the edible parts and discards of broccoli. Ultrasound processing is an emerging technology that produces these effects in foods, but has been poorly explored in broccoli so far. The aim of this work was to study the effect of ultrasound-assisted blanching on myrosinase activity and SFN content in broccoli florets. Myrosinase showed first-order inactivation kinetics in blanching at different temperatures with and without ultrasound processing. The inactivation rate was faster using ultrasound, with kinetic constants two orders of magnitude higher than without ultrasound. The activation energy (Ea) in traditional blanching (57.3 kJ mol−1) was higher than in ultrasound-assisted blanching (15.8 kJ mol−1). Accordingly, ultrasound accelerates myrosinase inactivation. The blanching time and temperature significantly affected myrosinase activity and SFN content. At 60°C and 4 min of ultrasound-assisted blanching, myrosinase activity was minimum and SFN content was the highest. These findings may help to design SFN enrichment processes and will contribute to the valorization of agro-industrial wastes. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.